Characterization of an Omnitrap-Orbitrap platform equipped with infrared multiphoton dissociation, ultraviolet photodissociation, and electron capture dissociation for the analysis of peptides and proteins - Smyrnakis, A; Levin, N; Kosmopoulou, M; Jha, A; Fort, K; Makarov, A; Papanastasiou, D; Mohammed, S (American Chemical Society, 2023)
We describe an instrument configuration based on the Orbitrap Exploris 480 mass spectrometer that has been coupled to an Omnitrap platform. The Omnitrap possesses three distinct ion-activation regions that can be used to perform resonant-based collision-induced dissociation, several forms of electron-associated fragmentation, and ultraviolet photodissociation. Each section can also be combined with infrared multiphoton dissociation. In this work, we demonstrate all these modes of operation in a range of peptides and proteins. The results show that this instrument configuration produces similar data to previous implementations of each activation technique and at similar efficiency levels. We demonstrate that this unique instrument configuration is extremely versatile for the investigation of polypeptides.